1994
DOI: 10.1128/aem.60.2.416-426.1994
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Comparisons of Chromosomal Types within an Indigenous Soil Population of Rhizobium leguminosarum bv. trifolii

Abstract: Host-specific ineffectiveness on Howard subclover SU298 (= ANU843) Unknown Molecular model strain of R leguminosarum bv. trifolii WA67 Australia Successful subclover inoculant under extreme conditions CC2238b Israel Competitive and persistent nodule occupant of subclover 9 RBL5280 (= RCR5 (= LPR5045) Unknown Molecular model strain of R leguminosarum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Wayne et al (1987) suggested that a species 'would include strains with approximately 70% or greater DNA-DNA relatedness.' Previous studies have shown a strong correlation between DNA-DNA hybridization values and estimates of genetic relatedness based on MLEE (Selander et al Leung et al 1994a). Based on our MLEE results, the genetic distance between Ei Ts 1 & 2, ET 3, ETs 4-8 and ETs 9-17 indicates that there may be u p to four species within this population.…”
Section: Discussionmentioning
confidence: 93%
“…Wayne et al (1987) suggested that a species 'would include strains with approximately 70% or greater DNA-DNA relatedness.' Previous studies have shown a strong correlation between DNA-DNA hybridization values and estimates of genetic relatedness based on MLEE (Selander et al Leung et al 1994a). Based on our MLEE results, the genetic distance between Ei Ts 1 & 2, ET 3, ETs 4-8 and ETs 9-17 indicates that there may be u p to four species within this population.…”
Section: Discussionmentioning
confidence: 93%
“…chvA and chvB homologous to A. tumefaciens genes) for the early phases during plant colonisation in the di¡erent plant-associated bacteria [50]. Two of the remarkable characteristics of plant-associated bacteria are their high genetic diversity found world-wide and their clonal population structure encountered in speci¢c ecosystems [52,56,64,65].…”
Section: Local Adaptations and Plasmidsmentioning
confidence: 99%
“…However, the nature of ecotypic structure is poorly understood for most bacterial populations, both because the relevant environmental niche differences are often unknown and because there are few data on the distribution of ETs across specific habitats. For symbiotic nitrogen fixing bacteria, a number of studies have characterized patterns of genetic diversity using multilocus enzyme electrophoresis (Young 1985;Pinero et al 1988;Eardly et al 1990;Souza et al 1992;Leung et al 1994, Souza et al 1994). However, most previous work has not examined intrapopulation associations between bacterial ETs and host plants.…”
Section: Bacterial Genotypes In Other Populationsmentioning
confidence: 99%